Analisis Perhitungan Biaya Produksi Menggunakan Metode Full Costing Sebagai Dasar Penentuan Harga Jual Produk - Ammi Nadira, Daffa Aqila; Nusantoro, Jawoto; Febri Darmayanti, Elmira (Universitas Muhammadiyah Metro, 2025)
This research aims to analyze the calculation of production costs using the full costing method as a basis for determining product selling prices at the